Curcumin ameliorates oxidative stress in animal models of multiple sclerosis - Laleh Mavaddatiyan; Shiva Khezri; Meysam Abtahi Froushani (Fasa University of Medical Sciences, 2019)
Background & Objectives: The role of oxidative stress in the pathogenesis of Multiple Sclerosis (MS) has been mentioned in previous studies. Curcumin is an active ingredient in Curcuma longa and has anti-inflammatory properties. The aim of this study was to investigate the effects of curcumin on reducing the oxidative stress in the animal model of MS. Materials & Methods: In this study, experimental autoimmune encephalomyelitis (EAE) as a MS model was induced by immunizing of Wistar rats (n=12) with homogenized spinal cord of guinea pig and Freund's complete adjuvant. Then, the immunized animals were divided in two equal groups. Treatment was curcumin (100 mg/kg daily) was started from the day 12 after the immunization when the rats showed the first symptoms of neurologic disability and continued until the day 24 when the rats were sacrificed. Simultaneously, the control group received the distilled water. Treatment was continued until 24 days after the immunization. Results: The consumption of curcumin in the EAE-treated rats caused a significant decrease in nitric oxide level and activity of serum myeloperoxidase enzyme activity (p<0. 05). At the same time, the malondialdehyde level in the brain tissue decreased (p<0. 05). However, no significant change in the total antioxidant capacity of the serum (p<0.05) was observed. Moreover, the serum uric acid level increased in rats after curcumin treatment and reached the level of healthy rats (p<0. 05). Conclusion: Using a 100 mg/kg curcumin in the rats with EAE cause to reduce the harmful effects of oxidative damage and can be effective in MS treatment.